The extremophile Picrophilus torridus carries a DNA adenine methylase M.PtoI that is part of a Type I restriction-modification system - Gulati, Pallavi; Singh, Ashish; Goel, Manisha; Saha, Swati (Frontiers in Microbiology, 2023)
DNA methylation events mediated by orphan methyltransferases modulate various cellular processes like replication, repair and transcription. Bacteria and archaea also harbor DNA methyltransferases that are part of restriction-modification systems, which serve to protect the host genome from being cleaved by the cognate restriction enzyme. While DNA methylation has been exhaustively investigated in bacteria it remains poorly understood in archaea. Picrophilus torridus is a euryarchaeon that can thrive under conditions of extremely low pH (0.7), and thus far no reports have been published regarding DNA methylation in this extremophile. This study reports the first experimentation examining DNA methylation in P.torridus. We find the genome to carry methylated adenine (m6A) but not methylated cytosine (m5C) residues. The m6A modification is absent at GATC sites, indicating the absence of an active Dam methylase even though the dam gene has been annotated in the genome sequence. Two other methylases have also been annotated in the P.torridus genome sequence. One of these is a part of a Type I restriction-modification system. Considering that all Type I modification methylases characterized to date target adenine residues, the modification methylase of this Type I system has been examined. The genes encoding the S subunit (that is responsible for DNA recognition) and M subunit (that is responsible for DNA methylation) have been cloned and the recombinant protein purified from E.coli, and regions involved in M-S interactions have been identified. The M.PtoI enzyme harbors all the nine motifs that typify Type I modification methylases, and displays robust adenine methylation in in vitro assays under a variety of conditions. Interestingly, magnesium is essential for enzyme activity. The enzyme displays substrate inhibition at higher concentrations of AdoMet. Mutational analyses reveal that Motif I plays a role in AdoMet binding, and Motif IV is critical for methylation activity. The data presented here lays the foundation for further research in the area of DNA methylation and restriction-modification research in this most unusual microorganism.